Field reports, August 1 through November 30, 1999, Pam and Reid Allen - Allen, Pamet al; Allen, Reid I.et al (1999)
An annotated list of birds sighted by Pam and Reid Allen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1999. Epson - sheet feed